2018
DOI: 10.5539/jfr.v8n1p32
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Micronutrient Contents of Callianassa turnerana from the Wouri Estuary, Cameroon

Abstract: Callianassa turnerana, called Cameroon ghost shrimps is shrimp with a great sociocultural interest in Cameroon. This study assessed proximate composition and micronutrients contents of Callianassa turnerana from the Wouri estuary in Cameroon. Adult shrimps were collected. The proximate composition, mineral, carotenoids and vitamin E contents were determined in edible parts (male and female) and in eggs of C. turnerana using official analytical methods. One way ANOVA and Fisher’s post hoc PLS test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The observed values on the other hand were generally higher than what was reported for some vegetables consumed in Nigeria [19] [20] and peels of plantains [4]. However, when compared to some animal samples, it was observed that the lipid levels of the raw and plantain chips samples were favourably comparable, for instance, male and female Callianassa turnerana (12.3% -13.0%) [21], and higher in some instances (flesh of male and female Neopetrolisthes maculatus) (4.05% -4.45%) [22] and Callnectes pallidus and Cardisoma armatum (1.65 -2.09%) [23].…”
Section: Resultsmentioning
confidence: 60%
“…The observed values on the other hand were generally higher than what was reported for some vegetables consumed in Nigeria [19] [20] and peels of plantains [4]. However, when compared to some animal samples, it was observed that the lipid levels of the raw and plantain chips samples were favourably comparable, for instance, male and female Callianassa turnerana (12.3% -13.0%) [21], and higher in some instances (flesh of male and female Neopetrolisthes maculatus) (4.05% -4.45%) [22] and Callnectes pallidus and Cardisoma armatum (1.65 -2.09%) [23].…”
Section: Resultsmentioning
confidence: 60%